2002
DOI: 10.1063/1.1465130
|View full text |Cite
|
Sign up to set email alerts
|

Effective method for stress reduction in thick porous silicon films

Abstract: A promising stress control process is demonstrated to achieve near-zero stress levels in thick porous silicon (PS) films. Stress reduction is necessary for thick PS structures to be used for radio-frequency applications such as on-chip inductors and transmission lines that require very thick (>100 μm) insulating materials. This study employs a standard sample structure with 50-μm-thick PS films formed on p+ substrates through anodization under 50 mA/cm2 and 25% HF concentration. Mass spectroscopy analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…The data shows two peaks in the desorption of hydrogen with increase of annealing temperature, starting at ~350 ˚C. However the data in Figure 5 have measured an increase in tensile stress [6,7], supporting our observation of the role that N 2 plays in this region. In region C, significant dihydride desorption occurs from the pore walls, so that upon removal from the thermal annealer to undertake measurements (as was done here), oxidation occurs which increases the compressive stress.…”
Section: Nitrogen Vs Vacuum Annealing Effects On Stresssupporting
confidence: 83%
See 2 more Smart Citations
“…The data shows two peaks in the desorption of hydrogen with increase of annealing temperature, starting at ~350 ˚C. However the data in Figure 5 have measured an increase in tensile stress [6,7], supporting our observation of the role that N 2 plays in this region. In region C, significant dihydride desorption occurs from the pore walls, so that upon removal from the thermal annealer to undertake measurements (as was done here), oxidation occurs which increases the compressive stress.…”
Section: Nitrogen Vs Vacuum Annealing Effects On Stresssupporting
confidence: 83%
“…After annealing, the PS Bragg peak shifted away from its original position. Moreover, the peak for the sample annealed at 300 ˚C moved to the right of the Si peak, indicating the film became tensile as predicted by previous results [6]. However, the peak moved back to within 3×10 -3 degrees of the original peak after the HF dip.…”
Section: Stress Measurements In Ps With X-ray Diffractionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, it should be noted that most of the studies have concentrated on changes of the chemical state of internal surfaces and the related strain and stress evolution in PSi films during thermal annealing, without suggesting a solution to control the stress. The real deal how to control the stress in PSi films was made only by Kim et al (2002). The approach proposed by Kim et al (2002) consisted of multithermal annealing and oxidation cycles.…”
Section: Stress Reduction In Porous Siliconmentioning
confidence: 99%
“…38 Kim et al reported an effective annealing process to reduce significantly stress in thick pSi films. 39 But, this technique requires a precise control of the temperature and annealing ambient (N 2 and O 2 ).…”
Section: B Etching Of High Porosity Thick Ps Layersmentioning
confidence: 99%